2015
DOI: 10.1016/j.jaapos.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Macular optical coherence tomography in patients with unilateral optic nerve hypoplasia

Abstract: PURPOSE To characterize the extent and location of macular thinning in patients with unilateral optic nerve hypoplasia (ONH) as compared to the contralateral normal eye. METHODS The medical records of patients with unilateral ONH who underwent spectral domain optical coherence tomography (SD-OCT) of the macula were retrospectively reviewed. SD-OCT scans were manually segmented by 3 observers in 3 macular regions (superior, central, inferior). Boundaries identified included the inner limiting membrane, the ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Abbasian et al . have shown that unilateral isolated optic nerve hypoplasia, represented by a decrease in the number of axons within the optic nerve, is associated with subclinical outer retinal abnormalities due to trans-synaptic degeneration 7 . Park et al .…”
Section: Introductionmentioning
confidence: 99%
“…Abbasian et al . have shown that unilateral isolated optic nerve hypoplasia, represented by a decrease in the number of axons within the optic nerve, is associated with subclinical outer retinal abnormalities due to trans-synaptic degeneration 7 . Park et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is the best in patients with grade 1 hypoplasia, and it gradually decreases in more severe grades [4]. Foveal hypoplasia, as already mentioned, can be isolated, similarly to isolated optic nerve hypoplasia, or associated with systemic abnormalities and preterm birth [4][5][6][7]. The OCT examination is conclusive in establishing the diagnosis of developmental anomalies of the macula, which can result in visual dysfunction and other ocular abnormalities, such as nystagmus.…”
Section: Resultsmentioning
confidence: 99%